Strategi Komunikasi Digital Partai Pan Dalam Membangun Kampanye Dengan Memanfaatkan Media Sosial - Parameswari, Dinar Mahkota; Qoni’ah Nur Wijayanti, S.Ikom., M.Ikom (PT. Media Akademik Publisher, 2024)
In this study, researchers analyzed the digital communication strategy of the Partai Amanat Nasional (PAN) in building a campaign by utilizing social media. The expansion of political participation through social media is a key element of the political communication strategy used by PAN. With a membership consisting of a number of well-known artists, the party has managed to build a positive image in the eyes of the public, aiming to promote nationalism and religious values in various political events. This research uses a qualitative method of descriptive approach to understand a strategy. The researcher analyzes how PAN has successfully used social media as an important tool in political campaigns, while managing issues such as the spread of false information and negative campaigns that can trigger social polarization and tension. The research discusses in detail the various strategies used by PAN, including engaging content such as short videos, short stories, which are effective in attracting a wide audience. By focusing on the role of social media in raising people's political awareness, this research provides valuable insights into the role of political communication in Indonesia's modern political context. Keywords: Political Party, Campaign, Political Communication, Social Media